oblicz korzystając ze wzorów skróconego mnożenia a) (1- 2x)³ b) (2 - x√3)³​

Odpowiedź :

Odpowiedź:

[tex]a)\ \ (1-2x)^3=1^3-3\cdot1^2\cdot2x+3\cdot1\cdot(2x)^2-(2x)^3=1-3\cdot1\cdot2x+3\cdot4x^2-8x^3=\\\\=1-6x+12x^2-8x^3\\\\\\b)\ \ (2-x\sqrt{3})^3=(2-\sqrt{3}x)^3=2^3-3\cdot2^2\cdot\sqrt{3}x+3\cdot2\cdot(\sqrt{3}x)^2-(\sqrt{3}x)^3=\\\\=8-3\cdot4\sqrt{3}x+6\cdot3x^2-\sqrt{27}x^3=8-12\sqrt{3}x+18x^2-\sqrt{9\cdot3}x^3=\\\\=8-12\sqrt{3}x+18x^2-3\sqrt{3}x^3[/tex]

Szczegółowe wyjaśnienie:

[tex](a-b)^3=a^3-3a^2b+3ab^2-b^3[/tex]

Viz Inne Pytanie